Numerical investigation on the effect of different strut angle to the cerebral aneurysm - Noor Harliana, A. Hamid (2009)
The objective of this study was to determine the correlation of stent strut angle to blood flow and also to determine the flow behavior in stented aneurysm. The computational fluid dynamics was applied to access the changes of velocity and pressure in aneurysms. For this study, there are five stent with the same design but different in strut angle of the stent. The strut angle used in this study was 30°, 35°, 35°, 40°, 45° and 50°. By using 30° of strut angle as the control model and the other angle as the experimental model, there are referred to as type I, type II, type III and type IV. The simulation of the model was studied under incompressible, Newtonian, viscous and non-pulsatile condition. The results for all stents analyzed in the current study showed that the stent with higher angle are more efficient than stent with lower angle. The minimum velocity increased with the implacement of stent type IV which is the higher strut angle. Meanwhile, for the pressure distribution of all type of stents indicate that lowest peak pressure obtained by stent type III. Therefore, strut angle used should be suitable to satisfy the requirement of lowest peak pressure and highest minimum velocity. So, the strut angle has to be maintained within a certain range, which varies from 40° to 45°. Finally, the correlation obtained from this numerical result could be used to investigate the pressure distribution around the aneurysms.